THE IMAGE AS TEACHING OBJECT - Proença Lara, Glaucia Muniz (Laboratório Editorial FCL-UNESP, 2011)
This paper aims to present an approach for visual and syncretic texts in the classroom, resorting to the principles and methods proposed by the French Semiotics, mainly by one of its most recent branches: the Visual or Plastic Semiotics. Thus, the text is analyzed through the articulation between content and expression so as to allow, whenever it is pertinent, the homologation of categories issued from both plans, which is responsible for the construction of semi-symbolic relations. Semi-symbolism offers a new reading of the world when it associates directly relations of colour, of form (expression plan) to meaning relations (content plan), contributing, in this way, to change the student into a proficient reader of texts/images.